Gracilaria changii (Rhodophyta) alleviates bisphenol A-induced adverse reproductive abnormalities in mice - Kwong, P. J.; Ng, C. L.; Tan, G. C.; Yow, Yoon Yen *; Gupta, M. K. (Hainan Medical University, 2021)
Objective: To evaluate the potential of Gracilaria changii extract in ameliorating the potential adverse effects of bisphenol A. Methods: The antioxidant capacity of Gracilaria changii extracted using different solvents (methanol, ethanol, and aqueous) was studied. The mice were administered by oral gavage with bisphenol A (60 mg/kg body weight) for 6 weeks with or without Gracilaria changii aqueous extract. Thereafter, the mice were either euthanized for histology and immunohistochemistry studies or mated to evaluate the pregnancy rate. Results: Gracilaria changii aqueous extract showed the highest antioxidant properties compared with extract using methanol and ethanol. The aqueous extract of Gracilaria changii improved the uterus index and uterine lipid peroxidation after bisphenol A exposure, although the uterine expressions of estrogen receptors and complement C3 were not improved. Histological evaluation of the uterus during the estrus stage has revealed that the extract could mitigate bisphenol A-induced adverse effects in the uterus as there was a lower percentage of mice showing abnormalities like decreased eosin staining in the myometrium, and decrease in the number of eosinophil and endometrial glands in the endometrium. Besides, Gracilaria changii aqueous extract improved the pregnancy rate of mice administered with bisphenol A. Conclusions: Gracilaria changii extract protects against bisphenol A-induced female reproductive abnormalities in mice which may be mediated via modulation of eosinophil migration, endometrial gland formation, and protein expressions associated with prostaglandins in the myometrium.